Empoderamiento del currículo de matemáticas en los profesores de transición y primero como estrategia de mejoramiento (2019)
The curricular articulation from one grade to another, particularly in the initial transition and first grade education represents an important line in the understanding and improvement of the primary school classroom practices, especially in the official Colombian schools, where for multiple reasons, the Preschool is completed in a single year (Lozano, 2002, p.5). Understanding, and improving the classroom practices of these teachers, from the empowerment of the dynamics of the curriculum, in the aforementioned grades, has been the objective of this research. It was based on the characterization, through the construction of an action plan, later the reflection that enabled the implementation of improvement actions was reached. The scenario that concerns us in the present work is the Juan Acosta Solera Educational Institution, in Los Olivos II neighborhood, South West, of Barranquilla. For the execution of these actions, we use the methodology of AI, Research-Action, (Latorre, 200, p 25.), in order to empower the group of teachers, in the exercise of autonomy, self-determination, participation, and mobilization, (Narayan, 2005, p 57.). All this in four moments, namely, identification of the problem, preparation of the plan, implementation, and evaluation.Fundamental, it is, in these practices, where the dynamics of the changes that impact the curriculum are reflected, changes in theories, models and approaches, in terms of content, because the objectives are essentially perennial, since they respond to the intentions and purposes of the formation of Being. Although the nature of the contents of the curriculum, are assumed as axes of a dynamic gear, in practice today they are perceived as confusing, tacit responsible for results in students, and as an enigma to decipher when the diagnoses of the immediately higher degree are applied.